Reconstruct(ing) a Hidden History: Black Deaf Canadian Relat(ing) Identity - Jenelle Rouse; Amelia Palmer; Amy Parsons (Social Sciences, 2023)
Black Deaf Canadians are under-represented in every facet of life. Black Deaf Canadian excellence, history, culture, and language are under-documented and under-reported. Where are we in history? Where are we now? Why are we not being documented? Black Deaf Canada was established to address these long-standing issues and went on to create an independent research team that led a project called “Black Deaf History in Canada”. This article provides an early account of how the community-based research team conducted a relationship-building practice prior to and during a three-week research trip. Black Deaf Canadians’ relat(ing) experience in history has inspired us to fight for inclusivity.